High Level Student Autonomy in a Virtual Learning Environment - Allan, Barbara; Barker, Mike; Fairbairn, Kate; Freeman, Margaret; Sutherland, Pam (Proceedings of the International Conference on Networked Learning, 2002)
This case study explores the experiences of a group of students (the authors) working as a tutor-less group (TLG) that developed during a web-based MEd programme. We describe the development and life cycle of the TLG, the experiences of the students and the effects on those who continued to work in a tutored environment. Members of the TLG demonstrated high levels of autonomy and group work. The relationship between the TLG and communities of practice is considered.